Determinants of Disclosure Noncompliance and the Effect of the SEC Review: Evidence from the 2006 Mandated Compensation Disclosure Regulations - Robinson, John R.; Xue, Yanfeng; Yu, Yong (The Accounting Review, 2011)
ABSTRACT We investigate the economic forces that influence noncompliance with mandatory compensation disclosures and the effect of a subsequent focused enforcement action. We utilize SEC evaluations of compensation disclosures mandated by rules adopted in 2006 to examine whether noncompliance is associated with excess CEO compensation, proprietary costs, or previous media attention. We further test whether subsequent CEO compensation declines after the SEC publicly identifies noncompliance. We construct measures of defective disclosures from SEC critiques and find that disclosure defects are positively associated with excess CEO compensation and media criticism of CEO compensation during the previous year. We find no evidence supporting the contention that compensation disclosure defects are associated with proprietary costs. Furthermore, we are unable to document that the level of disclosure defects identified by the SEC is associated with a reduction in excess CEO compensation in the subsequent year. Data Availability: Data are available from public sources identified in the paper. JEL Classifications: M52, G32, G38.